Study of Exemplary Guidance Programs in Elementary Schools. OEA Evaluation Report - Solomon, Henry; New York City Board of Education, Brooklyn, NY. Office of Educational Evaluation ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Interest in guidance in the elementary school appears to be growing. Eight exemplary guidance programs were examined in order to identify effective approaches and strategies that could be replicated. A literature review suggested that counselors should spend less time modifying individual student behaviors and more time improving the learning environment. Interview and observation instruments were designed to collect data specifically pertaining to 10 ideal guidance practices identified in the literature review. Results showed that successful guidance programs operated as integral parts of schools' overall educational functions. These exemplary programs also provided a wide range of guidance services to their students, staff, and parents and served as the fulcrum for a variety of human resources for at-risk children and their families. Successful guidance programs were supported by faculties that were responsive and willing to share in the planning and implementation of guidance functions. Successful counselors served more children more effectively through active collaboration with community social service professionals and provided leadership and direction in the operation of school pupil personnel committees. Principals should bring counselors into schoolwide programming and decision-making, and greater initiatives should be exercised in building a strong parent constituency. (ABL)
Availability: Office of Educational Assessment, New York City Board of Education, 110 Livingston Street, Brooklyn, NY 11201.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Education; Elementary School Students; Elementary Schools; Program Effectiveness; School Counselors; School Guidance; Reports, Evaluative